Development of mural art (street art) after the last war in Kosovo - Muharremi, Agnesa; Muharremi, Ilir (SAUC - Street Art and Urban Creativity (repository), 2020)
This paper presents the development of graffiti art after the last war in Kosovo. From 2000 to 2020. The presented murals express emotions, contain satirical nuances, humor, ridicule of various political figures in the state of Kosovo. Except that the ugly spaces are decorated,through this art , artists have used it as a voice of revolt and disappointment by playing with humor to fix the current system. The colour of the graffiti have been analyzed with The content, the messages it contains , the forms and many other details..